Association of Polymorphism -31 G/C in the Survivin Gene Promoter With the Risk of Multiple Sclerosis Disease - S Rezazadeh; P Mohammadi Nejad (Armaghane Danesh Bimonthly Journal, 2019)
Abstract Background & aim: Multiple Sclerosis (MS) is an immune system-dependent disease with unknown causes and is one of the most important neurological disabling diseases in adults, where the myelin section of the nervous system is destroyed. The link between MS and apoptosis in patients shows that the expression of many genes involved in inhibiting the immune cell apoptosis, such as Survivin gene, which causes more activity in these cells and increases the cerebrospinal fluid damage, has increased. The aim of the present study was to investigate of Polymorphism-31 G/C in the Survivin gene promoter in patients with MS disease and to compare with healthy people and its association with the disease.